Indonesia’s Infrastructure Gap: How Singapore and China Assisting Indonesia’s Economic Development in the Joko Widodo Era - M. Habib Pashya; Silvanah; Muslihah Faradila (Journal of World Trade Studies, 2023)
This paper aims to analyse the contribution of Singapore and China, the two most prominent investors, to Indonesia’s economic development. Since the 1950s and 1960s, Indonesia has engaged with both nations and experienced dynamic relationships. Since President Jokowi was elected (2014-2024), the relations between Indonesia, Singapore, and China have increased, involving both countries in most projects in Indonesia. We use the qualitative method in this research, utilizing primary and secondary data to ensure our argument. In our findings, we have at least three key points. First, we underline that the historical relationship between Indonesia, Singapore, and China is the foundation of their ties in the modern era. Second, as a rising power, China has started and continued its engagement in Indonesia, together with their investment. At this point, the Belt and Road Initiative is pivotal. Lastly, we underscore that Singapore’s contribution to Indonesia is gigantic, for example, how Singapore offered investment in Kendal. We conclude that Singapore and China played significant roles in improving Indonesia’s economic development in every aspect.